The effect of enlightened leadership practices on organizational sustainability :An Analytical research in the colleges of the University of Baghdad - Rasol Mahdi*, Duaa; Jassim Mohammed, Alyaa (Journal of Economics and Administrative Sciences, 2024)
The current research aims to study the impact of enlightened leadership - represented by role model, developer, servant, communicator, visionary, changer - as an independent variable, on organizational sustainability - which includes direction, behavior, organization, guidance and evaluation. . As a dependent variable among a sample of university leaders. At the University of Baghdad. Knowing the extent of colleges’ interest in research variables and dimensions. The problem is limited understanding and use of enlightened leadership to achieve sustainability in the college environment. The research asks: Do informed leadership practices have an impact on organizational sustainability in the colleges of the University of Baghdad? What kind of relationship between them? The researcher used the descriptive analytical method in conducting the research and chose an ambitious sample of 160 respondents from leadership positions such as college deans, their assistants, and department heads. The primary analytical tool was the questionnaire. A total of 160 valid questionnaires were collected for statistical analysis. The researcher also used personal interviews and various statistical programs, including SPSS V25, to extract primary data. Using descriptive and inferential statistical methods, including validity and reliability testing, confirmatory factor analysis, calculating means and standard deviations, and the Pearson correlation coefficient, the researcher reached several conclusions. One of the key outcomes was the overall trend of colleges at the University of Baghdad towards enhancing their organizational sustainability by adopting informed, innovative, service-oriented leadership and improving assessment.Research paper.